Meningkatkan Hasil Belajar Menggunakan Metode Diskusi Kelompok Mata Pelajaran Pai Dan Budi Pekerti di SMAN 1 Basa Ampek Balai - Putri, Rani Soraya (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students’ learning outcomes in Islamic Education through the implementation of group discussion methods. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The results indicate that in the first cycle, students were still passive in asking questions and expressing opinions. However, in the second cycle, after improvements and reinforcement, students showed significant progress in participation and learning outcomes. The average student score increased from 56.14 in the pre-cycle, to 71.81 in the first cycle, and 84 in the second cycle. Therefore, it can be concluded that the group discussion method is effective in improving students’ learning outcomes in Islamic Education.